IMPLEMENTASI VISI MISI BUPATI INDRAGIRI HULU DALAM PENGELOLAAN DESTINASI WISATA DI KABUPATEN INDRAGIRI HULU TAHUN 2022 - Rachman, Gieat Fathur; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indragiri Hulu Regency is an area that is rich in natural potential, historical value, arts and culture and has a variety of tourism potential that can be developed. The Indragiri Hulu Regency government is also aware of the huge potential of tourist destinations, which is reflected in the Vision and Mission of the Regent of Indragiri Hulu 2021-2026. The Vision of the Regent of Indragiri Hulu 2021-2026 is "Creating Integration for a More Prosperous Indragiri Hulu Community" and one of the Missions of the Regent of Indragiri Hulu 2021-2026 focuses on "Integrated Tourism and Creative Economy Development". However, it was reported that the vision and mission had not been implemented optimally due to the lack of optimal tourist destination management programs and inadequate funding. The theory used in this research is Political will from Derick (1999). This research aims to find out why the Regent of Indragiri Hulu did not make the tourism sector a priority sector in the development plan for Indragiri Hulu district in 2022, to find out the commitment to the vision and mission of the Regent of Indragiri Hulu regarding tourism and to find out the allocation of funds for Indragiri Hulu tourism in 2022. The data used in this research refers to data collected from interviews, field observations, and documentation supported by data published by several related agencies. The research indicators are program evaluation of the implementation of the Indragiri Hulu Regent's vision and mission, government initiatives, priorities, mobilization of political and public support, policies, fund allocation, continuity and adaptation. This data shows that the tourism sector is designated as a preferred sector as explained in the Government Regulation of the Republic of Indonesia No. 32 of 2004 and Law no. 23 of 2014. Even though it is a selected government affairs sector, the development and management of tourist destinations is one of the leading programs. However, the implementation of the vision and mission cannot be said to be optimal, especially with the minimal allocation of funds for Indragiri Hulu tourism in 2022. The government is committed to maximizing the implementation of the vision and mission in the future through several alternative initiatives. Keywords: Tourism, Indragiri Hulu, Vision and Mission